DIGITAL DA'WAH MODEL BASED ON E-ROHANI PLATFORM IN BUILDING THE INTEGRITY OF HUMAN RESOURCES OF THE INDONESIAN NATIONAL POLICE (POLRI) - istajib istajib; Nuri Nurhaidah (CV. Syntax Corporation Indonesia, 2023)
Discussing the theme of the historical construction of the Qur'an (târîkh Al-Qur'ân) is both interesting and challenging. It is interesting because this discussion will guide a reviewer on a series of scattered information related to the history of the Qur'an. For Qur'anic scholars who take a keen interest in this field, they will certainly be motivated to parse and frame each piece of data and information into a valuable monument of discourse on the history of the Qur'an. Interestingly, this study will arouse the passion of faith of a Muslim scholar to try to stem any current of discourse that has the potential to break the wall of faith in the revelation of the Qur'an. But on the other hand, this study can ignite a spark of discourse that is a little bolder because this discussion also presents a variety of information that sometimes collides with each other and demands the accuracy of a researcher. The reviewer who is lulled by the amount of data and sometimes negates each other may be trapped in a labyrinth space because of confusion in determining the right direction.